A comparative study of the growth indicators of infants born before and during the Covid-19 pandemic - Ali Omidian; Arghavan Afra; Mohammad Javad Golabvand; Maryam Ban; Naser Kamyari; Shima Seneysel Bachari (Clinical Epidemiology and Global Health)
Introduction: Growth disorders pose significant mental and physical health challenges with long-term complications for children. As monitoring children's growth is of paramount importance, in the present study attempts are made to compare growth indicators of infants from birth to 12 months before and during the outbreak of COVID-19 pandemic. Material and method: The present descriptive-analytical study was conducted using cluster sampling method in 10 comprehensive healthcare centers and on 200 infants in southwest of Iran during 2023. The infants’ health records and growth chart before and during the outbreak of COVID-19 pandemic served as data collection instruments. The collected data were analyzed using SPSS 21 software and descriptive and analytical statistics. Result: Economic hardship, job loss, maternal disease and neonatal acquired disease were found to be significantly higher during the pandemic outbreak compared to the pre-pandemic time. The average weight and BMI of the infants in both groups showed no significant difference from birth to two months old, but the difference was found to be significantly higher from 4 months to 1-year-old among infants born during the pandemic (P-value<0.05). Result this study showed that during the pandemic trend of The age of word articulation by infants was increasing (P-value = 0.022) and at this time 6 cases of missed vaccination were observed. Conclusion: The results indicate that the COVID-19 pandemic can affect the growth and development of infants, and may, in some cases, disrupt the growth and routine vaccination schedule during infancy and breastfeeding, which should be prevented by proper parental training.